2023
DOI: 10.1021/jacs.2c13188
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Azlactone Intermediate Drives Fungal Secondary Metabolite Cross-Pathway Generation

Abstract: Pathogenic fungi of Aspergillus section Fumigati are known to produce various secondary metabolites. A reported isolation of a compound with an atypical carbon skeleton called fumimycin from A. fumisynnematus prompted us to examine a related fungus, A. lentulus, for production of similar products. Here we report the isolation of fumimycin and a related new racemic compound we named lentofuranine. Detailed analyses revealed that both compounds were assembled by a nonenzymatic condensation of a polyketide interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recent work by Watanabe et al beautifully illuminated the biosynthesis of the fungal natural products fumimycin and lentofuranine 28 . These compounds arise from a phenolic intermediate of the terrein biosynthetic pathway, which, upon oxidative dearomatization, gives a quinone that reacts with fumarylazlactone 31 in a cross-pathway non-enzymatic condensation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Watanabe et al beautifully illuminated the biosynthesis of the fungal natural products fumimycin and lentofuranine 28 . These compounds arise from a phenolic intermediate of the terrein biosynthetic pathway, which, upon oxidative dearomatization, gives a quinone that reacts with fumarylazlactone 31 in a cross-pathway non-enzymatic condensation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…containing biosynthetic machinery to produce 1 and 2 discovered by Cox et al 2 , 3 , 5 also harbor highly similar, putative fumarylazlactone NRPSs encoding genes. For example, the genome of Penicilium rubens Wisconsin 54–1255 (GenBank GCA_000226395.1, assembly PenChr_Nov2007) 29 encodes the complete set of sorbicillin biosynthetic enzymes, namely the PKS biosynthetic enzymes SorA (accession number B6HNK3.1) and SorB (B6HN77.1), the FAD-dependent monooxygenase SorC (B6HN76.1), as well as the enzyme SorD (B6HNK6.1) 2 , 3 , 5 , together with an unassigned enzyme with high homology to putative fumarylazlactone NRPS biosynthetic enzymes from Aspergillus novofumigatus IBT 16806 (XP_024680046.1), A. fumigatus Af293 (XP_748654.2), and A. udagawae (XP_043143650.1) (>64% identity at the protein sequence level) 28 . While their interplay to complete the biosynthetic assembly of 7 remains to be experimentally proven, this, together with our chemoenzymatic access to 7 fusing sorbicillinol ( 2 ) and 31 in a highly stereoselective manner, strongly suggests that 7 is biosynthetically formed analogously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the optical rotation of natural 25 was much smaller than that of optical pure 25 , suggesting the biosynthesis of 25 involves a spontaneous racemization step. In 2023, our group isolated 25 and structurally-related compound lentofuranine ( 26 ) from A. lentulus and Aspergillus novofumigatus [ 26 ]. The stereochemistry of 26 was determined using Marfey’s method [ 27 ], revealing that 26 was also a racemic compound.…”
Section: Biosynthesis Of Fumimycin and Lentofuraninementioning
confidence: 99%
“…These results clearly indicated that AlsidE is responsible for the production of 31 . To our knowledge, this was the first report of azlactone-synthesizing NRPS [ 26 ]. Since azlactones are highly reactive compounds, this naturally occurring azlactone had been overlooked for a long time.…”
Section: Biosynthesis Of Fumimycin and Lentofuraninementioning
confidence: 99%